Metrics of sensory motor coordination and integration in robots and animals : how to measure the success of bioinspired solutions with respect to their natural models, and against more 'Artificial' solutions? /: how to measure the success of bioinspired solutions with respect to their natural models, and against more 'Artificial' solutions?. ([2020]) - Unknown
No abstract available